Program Kemahasiswaan Dalam Pemenuhan Indikator Kinerja Utama (IKU) Perguruan Tinggi – Best Practice - Libianko Sianturi; Sindak Hutauruk; Mula Sigiro; Hamonangan Siallagan; Jamser Simanjuntak (LPPM Universitas HKBP Nommensen, 2023)
Higher education KPI consist of eight indicators that measure the quality of graduates, lecturers, and curriculum. Based on the BK2PTKI invitation letter No. 07/BK2-PTKI/X/2022 dated 18 October 2022, the author was invited to attend as speakers with the topic: